The antidepressant drugs fluoxetine and duloxetine produce anxiolytic-like effects in a schedule-induced polydipsia paradigm in rats: enhancement of fluoxetine's effects by the α2 adrenoceptor antagonist yohimbine. Issue 5 (August 2015) - Prus, Adam J.; Mooney-Leber, Sean M.; Berquist II, Michael D.; Pehrson, Alan L.; Porter, Nicholas P.; Porter, Joseph H.
Abstract : Similar to the time-course for treating depression, several weeks of administration are required for serotonin (5-HT) reuptake inhibitors to produce anxiolytic effects. Previous studies with the schedule-induced polydipsia paradigm (a putative preclinical anxiety model) have shown that repeated administration of antidepressant drugs is necessary to produce a suppression of polydipsia, which is interpreted as an anxiolytic-like effect. The present study sought to expand past findings by evaluating the selective 5-HT reuptake inhibitor (SSRI) fluoxetine and the 5-HT-norepinephrine reuptake inhibitor duloxetine in the schedule-induced polydipsia paradigm with rats. Dose combinations of the α2 adrenoceptor antagonist yohimbine with fluoxetine were also explored to determine whether α2 adrenoceptor antagonism could enhance the anxiolytic-like effects produced by an SSRI. Fluoxetine and duloxetine significantly reduced water intake over the course of daily administrations. Daily treatment with the combination of fluoxetine and yohimbine produced a significantly greater reduction in water intake than fluoxetine alone. The present results confirmed previous findings that inhibition of 5-HT reuptake reduces water consumption in this paradigm. The results for the α2 antagonist yohimbine (in combination with fluoxetine) also indicate that α2 adrenoceptor antagonism may significantly enhance anxiolytic-like effects of SSRIs.